(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe patient characteristics, treatment outcomes, and postoperative quality of life assessed by EORTC QLQ-CR29 in rectal cancer patients undergoing laparoscopic low anterior resection. Methods: A descriptive study on rectal cancer patients treated with laparoscopic low anterior resection at E Hospital, from 2021 to 2024. Data included baseline characteristics, disease stage, operative outcomes, short- and long-term postoperative results. Quality of life was evaluated at 3 months post-operation using EORTC QLQ-CR29. Results: Forty-eight patients were included, mean age was 67.27 ± 10.18 years (40-85 years old), and 60.42% were male. Mean operative time was 201.04 ± 44.25 minutes (110-290 minutes) with a 2.08% conversion rate. Common postoperative complications included bowel sub-obstruction (6.25%), surgical site infection (4.17%), and anastomotic leak/dehiscence (4.17%). Mean follow-up was 15.38 ± 8.92 months; local recurrence occurred in 6.25%, distant metastasis in 20.83%, and mortality in 6.25%. QLQ-CR29 highlighted clinically relevant burdens in urinary, anorectal, stoma-related, and sexual domains, with differences between stoma and non-stoma groups. Conclusion: Laparoscopic low anterior resection yielded favorable outcomes with low conversion and acceptable morbidity. Quality of life assessment by QLQ-CR29 suggests the need for early screening and targeted management of urinary, anorectal, stoma-related, and sexual dysfunction after surgery.